Murine Models of Pancreatitis Leading to the Development of Pancreatic Cancer. Issue 1 (16th October 2018) - Leal, Ana S.; Liby, Karen T.
Abstract: Chronic or repeated episodes of acute pancreatic inflammation, or pancreatitis, are risk factors for the development of pancreatic cancer. Pancreatic cancer is characterized by a strong fibro‐inflammatory tumor microenvironment. In pancreatitis, the same fibro‐inflammatory reaction is observed concurrently with a loss of normal pancreatic cells. Mouse models are commonly employed to study the progression of pancreatitis and pancreatic cancer, with genetic and pharmacological tools used to elucidate cellular and acellular interactions within pancreatic tumors. Described in this article is a protocol for using Kras G12D ; Pdx1‐Cre (KC) mice stimulated with caerulein, a small oligopeptide that increases secretion of digestive enzymes, as a model for pancreatitis. KRAS is mutated in 90‐95% of the tumors in patients with pancreatic cancer. The combination of this mutation with an inflammatory stimulus accelerates the development of pancreatic cancer. The protocol detailed in this report follows the progression of disease in KC mice from pancreatic intraepithelial neoplasias to invasive pancreatic adenocarcinoma. © 2018 by John Wiley & Sons, Inc.